2021
DOI: 10.3390/antibiotics10060663
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds (VOCs) Produced by Gluconobacter cerinus and Hanseniaspora osmophila Displaying Control Effect against Table Grape-Rot Pathogens

Abstract: Table grapes (Vitis vinifera) are affected by botrytis bunch rot and summer bunch rot, the latter a complex disease caused by Botrytis cinerea, Aspergillus spp., Penicillium expansum and Rhizopus stolonifer. To search for biocontrol alternatives, a new bioproduct composed of Gluconobacter cerinus and Hanseniaspora osmophila, a consortium called PUCV-VBL, was developed for the control of fungal rots in table grapes. Since this consortium presents new biocontrol species, the effect of their VOCs (volatile organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…In this study, it was found that the VOCs produced by H. uvarum MP1861 could effectively suppress the mycelial growth of P. nicotianae FQ01. Consistent with our observations, production of VOCs with antifungal activities have been reported in various yeasts e.g., Candida intermedia (Huang et al, 2011), Hanseniaspora osmophila (Delgado et al, 2021), Starmerella bacillaris (Lemos Junior et al, 2020), Wickerhamomyces anomalus, Metschnikowia pulcherrima and Saccharomyces cerevisiae (Oro et al, 2018). In another report, the VOCs produced by H. uvarum reduced B. cinerea infection of strawberry (Qin et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, it was found that the VOCs produced by H. uvarum MP1861 could effectively suppress the mycelial growth of P. nicotianae FQ01. Consistent with our observations, production of VOCs with antifungal activities have been reported in various yeasts e.g., Candida intermedia (Huang et al, 2011), Hanseniaspora osmophila (Delgado et al, 2021), Starmerella bacillaris (Lemos Junior et al, 2020), Wickerhamomyces anomalus, Metschnikowia pulcherrima and Saccharomyces cerevisiae (Oro et al, 2018). In another report, the VOCs produced by H. uvarum reduced B. cinerea infection of strawberry (Qin et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that the volatiles produced by H. uvarum MP1861 contained ethyl acetate, isopentyl alcohol (1-butanol, 3-methyl-, acetate), and phenylethyl alcohol. Similarly, these volatiles were also detected in C. intermedia C410 (Huang et al, 2011 ) and H. osmophila 337 (Delgado et al, 2021 ). According to previous researches (Huang et al, 2011 ; Qin et al, 2017 ), these volatiles have been demonstrated antifungal activities.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Many publications have highlighted the phenomenon of the effects of volatile bacterial compounds on plants and fungi [ 50 ]. It is known that Serratia species produce different VOCs that play a role in the plant–microbe interactions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al, 2019b) or even the same species (Macías-Rubalcava et al, 2018;Guevara-Avendaño et al, 2019), but also some uniqueness by each one. Those conditions can be media composition (Fiddaman and Rossall, 1994;Bruce et al, 2004;Raza et al, 2015;Asari et al, 2016;Huang et al, 2018;Morita et al, 2019), media consistency (Dickschat et al, 2005;Qadri et al, 2015), period of incubation/growth stage (Weise et al, 2012;Giorgio et al, 2015;Sánchez-Fernández et al, 2016;Macías-Rubalcava et al, 2018;Misztal et al, 2018;Yang et al, 2019), humidity/water content (Jeleń, 2002;Misztal et al, 2018), temperature (Jeleń, 2002), oxygen and carbon dioxide levels (Zhang et al, 2013a), and interactions with other organisms (Sánchez-Fernández et al, 2016;Delgado et al, 2021). Such dynamicity and diversity of microbial VOCs can influence complex environmental trophic interactions (Fiedler et al, 2001;Bitas et al, 2013).…”
Section: Microbial Vocs At a Glancementioning
confidence: 99%